2022
DOI: 10.3389/fsufs.2022.997269
|View full text |Cite
|
Sign up to set email alerts
|

Long-term nutrient management in an intensive rice-wheat cropping system improves the quantities, qualities, and availability of soil sulfur

Abstract: In the last few decades, the deficiency of sulfur (S) has been noticed in the agricultural soils of India. Meanwhile, researchers reported that S plays a significant role in the productivity of the rice-wheat cropping system (RWCS). For the quantification of S response, a long-term field experiment was started at the Indian Council of Agricultural Research-Indian Institute of Farming Systems Research (ICAR-IIFSR), Modipuram, India. In total, 7 nutrient supply options were applied, i.e., organic, mineral fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Increment in yield and yield attributes due to full package supported by the essentiality of optimum cultivation practices required for obtaining the higher yield and evidenced the importance of individual cultivation practice to harvest maximum yield. The similar results with the findings of Jaybhay et al (2022) and Meena et al (2022). The yield gap in terms of yield reduction per hectare determined over the treatment full package was Efficiency of Factor Productivity and Effect of Individual Input of Production on Growth, Yield and Economics of Soybean.... recorded maximum under full package excluding weed management (388.0 kg ha -1 ) and full practice excluding RDF (254 kg ha -1 ) followed by full practice excluding insecticide application (233 kg ha -1 ).…”
Section: Yield Attributes and Yield Of Soybeansupporting
confidence: 91%
“…Increment in yield and yield attributes due to full package supported by the essentiality of optimum cultivation practices required for obtaining the higher yield and evidenced the importance of individual cultivation practice to harvest maximum yield. The similar results with the findings of Jaybhay et al (2022) and Meena et al (2022). The yield gap in terms of yield reduction per hectare determined over the treatment full package was Efficiency of Factor Productivity and Effect of Individual Input of Production on Growth, Yield and Economics of Soybean.... recorded maximum under full package excluding weed management (388.0 kg ha -1 ) and full practice excluding RDF (254 kg ha -1 ) followed by full practice excluding insecticide application (233 kg ha -1 ).…”
Section: Yield Attributes and Yield Of Soybeansupporting
confidence: 91%
“…When employing diverse organic amendments on rice and wheat, Hammad et al [ 65 ] ascertained that the soil's pH experienced a substantial increase upon the combination of chemical fertilizer and cattle manure. According to Meena et al [ 66 ], both organic and inorganic fertilizers made a notable contribution to the highest microbial biomass carbon (MBC). Bhardwaz et al [ 18 ] unveiled that the implementation of an integrated plant nutrition system exerted a positive impact on the soil's organic matter.…”
Section: Resultsmentioning
confidence: 99%
“…The highest organic and total S were found in the R-P-G system, which might be due to the lower crop removal compared to oilseedbased land use. The sulfur requirement is high for oilseed crops compared to cereals and other crops, and the inclusion of crops with high S requirement in the land use could deplete the soil S. Meena et al (2022) reported that the inclusion of pulses in the rice-wheat land use system could influence the availability of S. Shifting the virgin soils to cultivable lands with different agricultural management could change the equilibrium status of soil organic S and affect its distribution in surface layers (Solomon et al, 2003). Organic S accounted for an average of 93.5% of the total S, representing the dominant fraction in the soils.…”
Section: Influence Of Land Use On Soil S Fractionsmentioning
confidence: 99%